2022
DOI: 10.29026/oea.2022.210121
|View full text |Cite
|
Sign up to set email alerts
|

Label-free trace detection of bio-molecules by liquid-interface assisted surface-enhanced Raman scattering using a microfluidic chip

Abstract: Surface-enhanced Raman scattering (SERS), owing to its high sensitivity based on localized surface plasmon resonance of nanostructured metals, is recently attracting much attention to be used for biotechnology, such as cell imaging and tumor therapy. On the other hand, the trace detection of bio-molecules with large molecular weight is still challenging because the troublesome treatment of SERS substrate using coupling or cross-linking agents is required. In this paper, we apply liquid interface assisted SERS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 40 publications
0
48
0
Order By: Relevance
“…Surface-enhanced Raman scattering (SERS) spectroscopy has attracted great interest as a promising analytical technique for bimolecular detection due to its capability of label-free detection and high sensitivity. [1][2][3][4] Fleischmann et al first observed the Raman scattering signal of pyridine adsorbed onto the surface of roughened silver electrodes in 1974. 5 Further, with the development of processing techniques, SERS has acquired great strides and has been applied in numerous fields, such as surface science, electrochemistry, biomolecule detection, medical science, environmental monitoring, and food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-enhanced Raman scattering (SERS) spectroscopy has attracted great interest as a promising analytical technique for bimolecular detection due to its capability of label-free detection and high sensitivity. [1][2][3][4] Fleischmann et al first observed the Raman scattering signal of pyridine adsorbed onto the surface of roughened silver electrodes in 1974. 5 Further, with the development of processing techniques, SERS has acquired great strides and has been applied in numerous fields, such as surface science, electrochemistry, biomolecule detection, medical science, environmental monitoring, and food safety.…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant efforts to produce stable and uniform substrates with maximum number of effective hotspots to engender better SERS sensitivity [14] . Various plasmonic nanomaterials have been explored on rigid SERS substrates with limited onsite detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…There have been significant efforts to produce stable and uniform substrates with maximum number of effective hotspots to engender better SERS sensitivity. [14] Various plasmonic nanomaterials have been explored on rigid SERS substrates with limited onsite detection capabilities. Conversely, flexible SERS substrates offer easy sampling, scalability through printing and electrospinning, are low costing, making them ideal for translational sensing applications, especially when integrated as wearable SERS devices.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, surface-enhanced Raman scattering (SERS) spectroscopy is considered as a promising technique for the determination of trace heavy metal ions because of its special fingerprinting ability, high sensitivity, fast detection speed, and simple operation. The bottom-up approach is a simple and cost-effective strategy for fabricating SERS substrates, which mainly relies on the assembly of nanoparticle (NP) suspensions at the interface. , To date, using strong adsorbent surfactants to guide particle growth has produced a variety of noble metal NPs with different sizes, morphologies, compositions, or structures. On the other hand, the surfactants facilitate the separation of nanoparticles and ensure the stability of the NPs. Although the morphology of the synthesized NPs can be easily manipulated using surfactant molecules, their presence is problematic for the application of plasmonic sensing. Surfactant molecules bound to the surface of NPs act as physical and chemical barriers that restrict access of the analyte to the hot spot region, resulting in reduced Raman intensity of the analyte. , However, it remains a significant challenge to avoid the influence of surfactants on the adsorption of detection molecules by converting surfactant-free NPs to stable and reliable SERS substrates.…”
mentioning
confidence: 99%